(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This contribution presents a characterization of Barremian evaporite facies of the Neuquén Basin (western Argentina) in order to discuss accumulation processes and depositional conditions. The evapo- rite accumulation is related to a proto-Pacific trans- gression that followed an Early Barremian widespread desiccation event. These evaporites are known as the Upper Troncoso Member of the Huitrín Formation. They constitute a research topic of great importance, both from the theoretical point of view (stratigraphy, origin, palaeoclimate), as well as from the knowledge of non-renewable natural resources (celestine - barite, anhydrite - gypsum, rock salt, potassium salts and hydrocarbons). The Neuquén Basin is considered an ensialic backarc basin associated with the easterly oriented subduction along the proto-Pacific margin of Gond- wana (Figs. 1, 4). A generalised extensional stress regime due to steep subduction angle occurred in the magmatic arc and in the backarc settings, although regional thermal subsidence was punctuated by several episodes of structural inversion. Thus, the Upper Troncoso evaporites represent an unique example of accumulation in a marginal marine basin linked to the active continental margin of western Gondwana (Figs. 3, 4). The Lower Cretaceous deposits of the Huitrín Formation crop out almost continuously for more than 500 km along a north-south oriented belt (Fig. 5), from the latitude of the Aconcagua Mountain (Mendoza Province) up to the vicinity of the city of Zapala (Neuquén Province). Owing to the highest solubility and hygroscopic characteristics of the sediments, combined with the strong tectonic dis- turbation of the Huitrín Formation, the methodology for the study of the evaporites was largely based on subsurface information (geophysical well-log responses, cutting and cores) taken from oil and potassium salt exploration drill holes. In particular, electric logs allowed to identify electrofacies, and -based on the interpretation of cross-plots- to infer the mineralogy of the evaporites. Together with lithological descriptions of cutting and cores, repre- sentative samples of the rocks were studied in thin sections and by X-ray diffractometry. In the latter both whole-rock composition and <2µm clay mine- ral composition were defined. Lithological sections were elaborated, adjusted and correlated on the basis of this compositional information, and the areal distribution of evaporite salts was represented in a regional map. Geological correlations of the sedi- mentological record allowed define the geometry of evaporite facies in order to identify the main sedi- mentary environments. The regional study also involved the quantification of thickness variations in the deposits as well as the changes in evaporite mineralogy. The marine brine associated with the Troncoso evaporites followed successive processes of concen- tration and dilution. As a result, different salts were accumulated. In this study, these compositional changes are represented by the definition of several evaporite facies (Fig. 6). At the base of the Upper Troncoso Member the Facies Anhidrita was formed (Figs. 7, 8). This unit was covered by a thick salt succession composed of three facies: the lower Facies Salina Concentradora (Figs. 7, 9), the middle Facies de Sales Amargas (Figs. 10, 11), and the upper Facies Salina Terminal (Figs. 12, 13). During Facies Anhidrita deposition (Figs. 7, 8), the evaporite basin reached its maximum expansion (Fig. 14). An extensive salt pan formed from perennial or free brine, in the depocentral sector of the basin. Besides, a sabkha setting subjected to periodic events of flooding and concentration of the brines characterized the marginal areas of the basin. In this marginal belt, sulphate and carbonate microbial mats and siliciclastic muds were accumulated. In the central sectors of the basin, the anhydrite facies is characterized by microcrystalline films (sheets) composed of anhydrite-calcite pairs (Fig. 8), indicating a pelagic sedimentation under an almost stillness environment. A lateral transition from this central sector up to the coastal and supratidal sabkha sectors is recorded by regional correlation. In the lower part of the Facies Salina Concentra- dora, halite with a crystalline cumulus texture occurs (Figs. 7, 9). It was precipitated from a relatively depth brine and passes upwards to halite with a chevron texture indicating a progressive shallowing of the brine. The stratigraphic record of this facies shows cycles of primary clean halite – recycled halite – anhydrite sheets that repetitively occur. The Facies de Sales Amargas starts with sylvite daughter crystals in halite fluid inclusions, followed by a few crystals of sylvite, passing upwards to two thick beds of sylvinite (Fig. 10). This facies reaches a maximum thickness of 25 meters and represents the evaporite deposits of the Upper Troncoso Mem- ber with the smallest areal distribution (Fig. 14). However, they cover a (preserved) area of 3,000 km2. These deposits are dominated by sylvinite (sylvite plus halite), which appears as anhedral to subhedral reddish, yellowish and whitish crystal aggregates (Fig. 11). The presence of hematite as fine solid dispersions, suggests that sylvite would result from lixiviation of magnesium chloride from a primary red carnallite. The Facies Salina Terminal represents the dilution of the evaporite basin (Fig. 12). Three successive evaporite cycles are recognized and they are interpreted as the result of flash floods that supplied rainwater from emerged areas. The mix of these waters with the perennial brines in the depocenter allowed precipitation of an anhydrite bed followed by a rhythmic laminated succession of halite with chevron texture alternating with anhydrite. At this time, fine-grained siliciclastics would have been supplied to the evaporite basin through flash floods from emerged areas, as well as from pyroclastic activity in the magmatic arc. This terrigenous material was preferentially accumulated during the dilution of the evaporite brine. The peripheral sectors of the basin are represented by salty mudflat sediments or siliciclastic sabkha deposits, which are interpreted to represent the development of wet salt mudflats in coastal areas and relatively drier mudflats in the more proximal (continental) margins of the basin. Syn-depositional to slightly post-depositional changes occurred in both the central and marginal settings, where underground brines produced preci- pitation of inter-crystalline passive cement in clean halite, and dissolution – reprecipitation of halite in the chaotic mud salt (Fig. 9c). Early diagenetic processes also involved neoformation of evaporitic minerals (anhydrite by dehydration of gypsum and autigenous sylvite from carnallite). By hyperhalmyrolysis, smectite in fine-grained siliciclastic deposits was transformed in mixed layer clay minerals, namely chlorite and illite. Under the global Cretaceous greenhouse context, the Neuquén Basin supported a dry and windy climate. The magmatic arc would have acted as a topographic barrier to the open proto-Pacific Ocean, and the basin behaved as a partially isolated hydrographically depression below sea level at that time (Fig. 4). Therefore, the evaporites of the upper Troncoso Member are linked to a restricted marine environment; this is an inland hypersaline shallow sea. High temperatures generated strong evaporation rates, which exceeded water supply (runoff, ground water discharge and atmospheric precipitations). These conditions increased salt concentration and caused the precipitation of salts according to their degree of solubility (Fig. 16). Moreover, the conti- nuous evaporation would have created an imbalance in sea level currently stimulating continuous income, although limited, of sea water into the basin (Fig. 17a). In turn, the arc produced partial to total reflux retention in the basin, allowing brine concentration over time (Fig. 17a). A larger positive accommodation space towards the western sector of the depression favoured the connection between the proto-Pacific Ocean with the backarc Neuquén Basin during Facies Anhidrita and Facies Salina Concentradora (Fig.18). In the Facies Sales Amargas and in the Facies Salina Terminal, the evaporitic basin was assimilable to a hydrologically closed basin, with continental recharge of recycled marginal evaporites (Fig. 17b). This contribution identifies and characterizes a group of evapofacies in Barremian evaporites of the Neuquén Basin that allows to answer some questions on the origin, the depositional system, the controls and the evolution of the evaporitic record.